HUBUNGAN DIABETES MELLITUS PADA KLIEN YANG MENGGUNAKAN INSULIN DENGAN GEJALA OSTEOARTHRITIS DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG - Andoko Andoko; Dessy Hermawan; Rika Yulendasari (Universitas Malahayati Lampung, 2019)
ABSTRACT : DIABETES MELLITUS RELATIONSHIP IN CLIENTS USING INSULIN WITH SYMPTOMS OSTEOARTHRITIS IN DR. H. ABDULMOELOEK PROVINSI LAMPUNGYEAR 2018 Background : Based on data from Lampung Provincial Health Office, pravelensi of insulin-dependent diabetes mellitus in Lampung Province in 2015 amounted to 123 clients who were hospitalized, while client with outpatient as many 40 people. In 2016, the number of outpatient visits in patients with diabetes mellitus amounted to 28 people, while in hospitalization increased to 185 clients (Provincial Health Office of Lampung, 2016).Purpose : The purpose of this study is to know the relationship of diabetes mellitus in clients who use insulin with symptoms of osteoarthritis in RSUD Dr. H. Abdul Moeloek Lampung Province Year 2018.Method : This type of research is quantitative (non-experimental). The design of this study was an analytical survey using the cross sectional approach, the population of all diabetic patients using insulin in Dr. H. Abdul Moeloek Province 2018 as many as 214 people and got the number of samples of 59 respondents, the sampling technique in this study is simple random sampling, statistical test using chi-square test.Result : The result of chi square statistic test obtained P-Value α (0,02 0,05) then H0 is rejected. So it can be concluded there is a relationship of diabetes mellitus in patients who use insulin with the incidence oeteoartritis in RSUD Dr. H. Abdul Moeloek Lampung Province Year 2018 with Odds Ratio (OR) = 2.037.Conclusion : Suggestions can be used as an information and input material to improve the patient's knowledge of using insulin, which can affect weight gain, and affect lower extremity and muscle function, thus causing symptoms of osteoarthritis.Keywords: Diabetes Mellitus, Insulin, OsteoarthritisABSTRACT : DIABETES MELLITUS RELATIONSHIP IN CLIENTS USING INSULIN WITH SYMPTOMS OSTEOARTHRITIS IN DR. H. ABDULMOELOEK PROVINSI LAMPUNGYEAR 2018 Background :Based on data from Lampung Provincial Health Office, pravelensi of insulin-dependent diabetes mellitus in Lampung Province in 2015 amounted to 123 clients who were hospitalized, while client with outpatient as many 40 people. In 2016, the number of outpatient visits in patients with diabetes mellitus amounted to 28 people, while in hospitalization increased to 185 clients (Provincial Health Office of Lampung, 2016). Purpose :The purpose of this study is to know the relationship of diabetes mellitus in clients who use insulin with symptoms of osteoarthritis in RSUD Dr. H. Abdul Moeloek Lampung Province Year 2018.Method :This type of research is quantitative (non-experimental). The design of this study was an analytical survey using the cross sectional approach, the population of all diabetic patients using insulin in Dr. H. Abdul Moeloek Province 2018 as many as 214 people and got the number of samples of 59 respondents, the sampling technique in this study is simple random sampling, statistical test using chi-square test.Result :The result of chi square statistic test obtained P-Value α (0,02 0,05) then H0 is rejected. So it can be concluded there is a relationship of diabetes mellitus in patients who use insulin with the incidence oeteoartritis in RSUD Dr. H. Abdul Moeloek Lampung Province Year 2018 with Odds Ratio (OR) = 2.037.Conclusion :Suggestions can be used as an information and input material to improve the patient's knowledge of using insulin, which can affect weight gain, and affect lower extremity and muscle function, thus causing symptoms of osteoarthritis.Keywords: Diabetes Mellitus, Insulin, Osteoarthritis